2021
DOI: 10.1002/bsl.2515
|View full text |Cite
|
Sign up to set email alerts
|

Forensic psychiatric evaluation of 187 homicidal assailants with and without a schizophrenia spectrum disorder: Clinical, criminological and behavioral characteristics

Abstract: Intentional homicide, a declining phenomenon in Italy, represents one of the most extreme forms of violence. A specific subgroup of homicidal assailants is represented by those affected by mental disorders, where the relationship between psychopathology and characteristics of the homicidal attack is not yet fully understood. We analyzed the case files of 187 homicides or attempted homicides, in which the defendant had undergone a forensic psychiatric evaluation within the previous 10 years from a single forens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In addition, due to the retrospective nature of the data, important variables that have previously been considered critically important factors influencing homicides of individuals with SSD, such as the presence of psychopathy ( Fox & DeLisi, 2019 ) and adherence to (medication) therapy ( Baird et al, 2020 ; Carabellese et al, 2021 ) at the time of the offense, could not be examined. Another limitation is the small number of homicidal patients compared to other violent or non-violent patients in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to the retrospective nature of the data, important variables that have previously been considered critically important factors influencing homicides of individuals with SSD, such as the presence of psychopathy ( Fox & DeLisi, 2019 ) and adherence to (medication) therapy ( Baird et al, 2020 ; Carabellese et al, 2021 ) at the time of the offense, could not be examined. Another limitation is the small number of homicidal patients compared to other violent or non-violent patients in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, factors other than schizophrenia are claimed to predispose to crime, such as life events (physical abuse, parents’ criminal past, genetic factors), other dispositional factors (young age, male gender, lower income), or comorbid drug abuse ( 9 11 ). Researchers have found that crime is more common among people with mental illness who do not receive adequate treatment ( 12 ), whose pharmacotherapy is interrupted ( 13 ), or who actively experience delusions, paranoia ( 14 ), or hallucinations ( 6 , 15 , 16 ). The appropriate therapy and possible recovery of such patients pose many questions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this insight, the suicide rate is usually introduced as an index for assessment of mental health in the general population. Overall, 90% of suicide cases are associated with at least one mental health disorder such as psychosis or depression [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%